The crystal structure of dichlorido-[6-(pyridin-2-yl)phenanthridine-κ2N, N′]zinc(II)-chloroform (1/1), C19H13N2ZnCl5 - Tan Ban; Lai Ze-Yang; Wang Hai-Ping (Zeitschrift für Kristallographie - New Crystal Structures)
C19H13N2ZnCl5, monoclinic, I2/a, a = 15.2859(2) Å, b = 14.7894(1) Å, c = 18.0569(2) Å, β = 97.311(1)°, V = 4048.92(8) Å3, Z = 8, Rgt(F) = 0.0260, wRref(F2) = 0.0722, T = 296 K.